Corporate social responsibility and branding co-existence practices in Bank Simpanan Nasional and Agrobank in Malaysia - Ahmad Tarmidi, Nur Fadzila; Ariffin, Siti Nur Affni; Adzharuddin, Nor Azura (2016)
The growth of the relationship between companies and society has been one of deliberate transformation from philanthropic co-existences to one where mutual interest of the entire stakeholder is becoming essentially significant (Bhattacharyya & Rahman, 2003). Thus, it can be illustrated that corporate social responsibility (CSR) is in fact vital to organizations. Another essential part that relates to CSR is branding. A good brand can make customers trust and stay loyal to the products or services that they use. Today, many organizations are very concerned with the best brands to be presented to the public, in particular customers of the organization. Branding and CSR operate in synchrony. This is appropriate when market research shows responsible business practices to be key drivers of brand preference. Core strength of this is that companies with the right business model can tell a single compelling story across all touch points. It works best for those companies in which responsibility is (already) a core company value and informs all aspects of the business. This would mean a consistent performance across environmental, community, employee welfare, financial performance and corporate governance commitments. As such, this paper tries to show the importance of CSR and branding in general through certain examples of local organizations such as Bank Simpanan Nasional and AgroBank.